2013
DOI: 10.1021/nn404980k
|View full text |Cite
|
Sign up to set email alerts
|

Optically Controlled Thermophoretic Trapping of Single Nano-Objects

Abstract: Brownian motion is driven by thermal fluctuations and becoming more efficient for decreasing size and elevated temperatures. Here, we show that despite the increased fluctuations local temperature fields can be used to localize and control single nano-objects in solution. By creating strong local temperature gradients in a liquid using optically heated gold nanostructures, we are able to trap single colloidal particles. The trapping is thermophoretic in nature, and thus no restoring body force is involved. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
154
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 143 publications
(164 citation statements)
references
References 29 publications
3
154
0
1
Order By: Relevance
“…It has been demonstrated that the heat generated can benefit optical trapping by creating an electrothermoplasmonic flow that delivers nanoparticles to the trapping site 15 . Optical confinement of single nanoparticles or macromolecules has been achieved via a dynamic temperature field 16,17 . However, the particles or molecules in the dynamic temperature field undergo frequent and broad position fluctuations.…”
mentioning
confidence: 99%
“…It has been demonstrated that the heat generated can benefit optical trapping by creating an electrothermoplasmonic flow that delivers nanoparticles to the trapping site 15 . Optical confinement of single nanoparticles or macromolecules has been achieved via a dynamic temperature field 16,17 . However, the particles or molecules in the dynamic temperature field undergo frequent and broad position fluctuations.…”
mentioning
confidence: 99%
“…A similar argument holds for electrokinetic forces used in the ABEL trap. 22 Independent from the microscopic details that are hidden in the Soret coefficient, the balance of the thermodiffusive and diffusive current densities − ∇ ⃗ − ∇ ⃗ = D p D p T 0 T yields the steady state probability density distribution p(r⃗ ) for finding an object at a certain position of the temperature field T(r⃗ ) = T 0 + ΔT(r⃗ ). This probability density is given by the local temperature increment ΔT(r⃗ ) and the Soret coefficient, which is assumed to be temperature-independent.…”
mentioning
confidence: 99%
“…Despite its negative effects in plasmonic tweezing, the photothermal heating of plasmonic nanostructures can generate thermal gradients, which offer additional opportunities, such as thermophoresis, natural convection, and Marangoni convection, for powering nanomotors. The presence of a thermal gradient will force objects to move along or against the gradient, which is called thermophoresis .…”
Section: Nanomotor Movement Control Powered By Optical Resonancesmentioning
confidence: 99%
“…The photothermal heating of plasmonic nanostructures provides a convenient way to achieve the temporal and spatial control of the environmental temperature, and therefore enables various thermodiffusive movements of different nanomotors. For example, a hexagonal array of triangular Au patches, when illuminated by a 532 nm laser, induces a thermal profile with a low temperature in the hexagon's center and the highest temperature in the Au area (Figure a) . The thermal profile has been used to confine and transport Brownian nanomotors and biomolecules .…”
Section: Nanomotor Movement Control Powered By Optical Resonancesmentioning
confidence: 99%
See 1 more Smart Citation